2012
DOI: 10.1007/s10646-011-0843-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses of cancer-related genes in turbot Scophthalmus maximus and mussels Mytilus edulis exposed to heavy fuel oil no. 6 and styrene

Abstract: Recent spills in European waters have released polycyclic aromatic hydrocarbons, important components of heavy fuel oil, and the hydrocarbon styrene. Heavy fuel oil and styrene are classified as potentially genotoxic and carcinogenic. Here we investigate transcription of genes involved in cancer development in the liver of juvenile turbots and in the digestive gland of mussels exposed to heavy fuel oil and to styrene and after a recovery period. In turbot, oil produced a significant up-regulation of p53 and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…None of these mutations have been described before in invertebrates and neither in mammals nor fish affected by neoplasia (Lima et al, 2008;Rotchell et al, 2008). Even when the amount of analysed neoplastic individuals in this study was small and a larger sample size would be desirable to draw more robust conclusions, a high incidence of ras gene polymorphic variation was observed in cockles, as reported earlier in M. trossulus affected by neoplasia (Ciocan et al, 2006), in M. galloprovincialis and in M. edulis (Lima et al, 2008;Ruiz et al, 2012) although not at the same codons. The observed polymorphic variations and mutations in ras may indicate genomic instability in natural cockle populations with high prevalence of neoplasia.…”
Section: Medulissupporting
confidence: 46%
See 1 more Smart Citation
“…None of these mutations have been described before in invertebrates and neither in mammals nor fish affected by neoplasia (Lima et al, 2008;Rotchell et al, 2008). Even when the amount of analysed neoplastic individuals in this study was small and a larger sample size would be desirable to draw more robust conclusions, a high incidence of ras gene polymorphic variation was observed in cockles, as reported earlier in M. trossulus affected by neoplasia (Ciocan et al, 2006), in M. galloprovincialis and in M. edulis (Lima et al, 2008;Ruiz et al, 2012) although not at the same codons. The observed polymorphic variations and mutations in ras may indicate genomic instability in natural cockle populations with high prevalence of neoplasia.…”
Section: Medulissupporting
confidence: 46%
“…Up-regulation of P53 protein expression has been reported in M. edulis affected by DN . However, few studies have reported transcription levels of p53 in molluscs (Muttray et al, 2008(Muttray et al, , 2010Siah et al, 2008;Ruiz et al, 2012). In our study, cockles moderately affected by DN presented a significantly higher p53 transcription level when compared to healthy cockles.…”
Section: Medulismentioning
confidence: 39%
“…This gene represents an essential checkpoint in the G2 phase of mitosis, being able to inhibit the genomic instabilities associated with tumours (Hollander & Fornace, ). Upregulation of this gene has been reported in individuals subject to chemical (turbot; Ruiz, Orbea, Rotchell, & Cajaraville, ) and osmotic stress (salmon; Maryoung et al., ) for extended periods of time. It is possible that this DNA repair gene is acting as a regulator of cell proliferation in Step +3.0°C after gradual temperature increase across generations.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation was found after 3 days exposure to chemicals suggesting ras is still kept in the protooncogene form which is not as closely involved in the DNA repair process as p53. Ruiz et al [65] found no mutation in ras gene at the traditional hotspots, i.e. codons 12, 13 and 61 in mussels after exposure to heavy fuel and styrene, suggesting ras was still in proto-oncogene (inactive) form following exposure to these contaminants.…”
Section: Relative Expression Of P53 and Ras In Haemocytes Following Ementioning
confidence: 99%